2015
DOI: 10.1111/bju.12953
|View full text |Cite
|
Sign up to set email alerts
|

Clinical utility of 18F‐fluorocholine positron‐emission tomography/computed tomography (PET/CT) in biochemical relapse of prostate cancer after radical treatment: results of a multicentre study

Abstract: ObjectiveTo evaluate 18 F-fluorocholine positron-emission tomography (PET)/computed tomography (CT) in restaging patients with a history of prostate adenocarcinoma who have biochemical relapse after early radical treatment, and to correlate the technique's disease detection rate with a set of variables and clinical and pathological parameters. Patients and MethodsThis was a retrospective multicentre study that included 374 patients referred for choline-PET/CT who had biochemical relapse. In all, 233 patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
16
2
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(21 citation statements)
references
References 33 publications
2
16
2
1
Order By: Relevance
“…Though, PET/CT was able to detect PCa relapse in 43% (50/115) patients with low PSA values (< 2 ng/ml). According to data of other authors, PET/CT showed corresponding rates ranged from 19% to 55% [9,19,[21][22][23][24].…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…Though, PET/CT was able to detect PCa relapse in 43% (50/115) patients with low PSA values (< 2 ng/ml). According to data of other authors, PET/CT showed corresponding rates ranged from 19% to 55% [9,19,[21][22][23][24].…”
Section: Discussionmentioning
confidence: 76%
“…Rodado-Marina et al analyzed a group with comparable number of patients and reported 48% (111/233) [9]. In other studies, performed on larger and mixed groups of patients (both after RP and RT) as well, 11C/18F-Choline PET/CT results allowed to reveal PCa relapse in 62% (155/250), 65% (124/185), 74% (185/250) and 76% (129/170) [10][11][12][13].…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…27,[29][30][31] We found the best threshold values to predict PET/CT positivity to be a trigger PSA of 2.6 ng/mL, PSAV of 2.0 ng/mL/year, and PSADT of 4.4 months. In comparison, Rodado-Marina et al reported a trigger PSA of 3.5 ng/mL (sensitivity 64%, specificity 76%) and PSADT of six months (sensitivity 58%, specificity 58%) while Cimitan et al reported a sensitivity of 79.5% and specificity of 67% for a trigger PSA of 2 ng/mL.…”
Section: Discussionmentioning
confidence: 81%
“…Our study shows a detection rate of 63.3% for recurrence after localized treatment of PCa, similar to previous studies. 27,28 A large number of the positive PET/CTs were validated using pre-established criteria.…”
Section: Discussionmentioning
confidence: 99%